Exergy method of optimisation of a wavy plate indirect evaporative cooler. (15th November 2004) - Abbassi, A.; Aliehyaei, M.
The present paper deals with the performance optimisation of a wavy plate surface of indirect evaporative coolers with cooling capacities of 10, 25, 45 kW. Based on the minimum entropy generation rate and by applying a number of geometrical constraints, as well as using a search method, the optimum apparatus's dimensions and the secondary air discharge and the primary air mass flow rates are calculated. The numerical results show that, to increase the cooling load of an indirect evaporative cooler, the optimisation of the above mentioned parameters by this method can increase energy efficiency by up to 65%.